Hubungan Pernikahan Dini Dengan Pola Asuh Anak Dalam Keluarga Di Wilayah Kerja Upt Puskesmas Amparita Kabupaten Sidrap Tahun 2023 - Nurbaya, St.; Mastuti, Mastuti; Syahriani, Syahriani; Rosmawaty, Rosmawaty (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2024)
The research in this thesis aims to determine the relationship between early marriage and parenting in the family in the working area of the Upt Amparita Health Center, Sidrap Regency. This research is motivated by the phenomenon of early marriage that occurs in the working area of the UPT Amparita Health Center. The subjects of this study were couples who married at an early age who had children aged 1 - 3 years, here the number of respondent was 30 people.The type of research used in this research was quantitative descriptive research with a retrospective descriptive approach. The data collection techniques of this research were questionnaires and documentation, where researchers conducted home visits to early marriage couples by distributing questionnaires to be filled in and then documenting in the form of pictures for validity. while for data analysis techniques using the chi square test on SPSS 25.0 for windows.Based on the results of research and analysis, researcher concludes that: 1) Early marriage in the work area of UPT Puskesmas Amparita shows that a mother who has children aged 1 – 3 years enduring early marriage . 2) Parenting in the family in the work area of UPT Puskesmas Amparita shows that 20 repondents or 66,7% of the subjects apply Democratic parenting. 3) There is no relationship between early marriage and parenting in the family in the work area of UPT Puskesmas Amparita with a p value of 0.346>0.05.